A Preliminary Brief Report on the Therapeutic Orientation Questionnaire (TOQ): What Does a Discrepancy Between a Student’s Preferences for Theoretical Orientation Mean? - Nakao, Gen (Advances in Social Sciences Research Journal, 2022)
Therapists each hold a therapeutic orientation, and therapists are sometimes also patients. Anecdotal evidence suggests that therapists may have discrepant theoretical orientations qua therapist versus qua patient. In this current preliminary study, the author developed the Therapeutic Orientation Questionnaire (TOQ) to investigate the phenomenon of this discrepancy. Based on the qualitative analysis, several themes related to self-referential statement emerged. Future directions and practical implications were also discussed.